Properties of oriented strand board (OSB) from mix tropical species / Ahmad Fauzi Othman, Norhafizah Rosman and Wan Mohd Nazri Wan Abdul Rahman - Othman, Ahmad Fauzi; Rosman, Norhafizah; Wan Abdul, Wan Mohd Nazri (2007)
Development of lesser-known tropical species can provide tools to help forester to preserve virgin forest area and restore native eco-systems. OSB from fast growing and lesser-known tropical species in this study seem to have good potential for filling needs in various structural and exterior applications. However, this potential will depend on further research and improvements in physical and mechanical properties of the OSB. The main objective of the study is to develop and determine properties of oriented strand board from mix tropical species (lesser-known and fast growing) as a raw material in the manufacturing of OSB.Species like Ludai, Mahang, Acacia mangium and leucaena leucocephala were found by this study to be a suitable alternative raw material since the result showed that most of the treatments meet the minimum requirement of mechanical and physical properties. It can be deduced from this study, that mixing Ludai and Mahang, acacia mangium and leucaena leucocephala from fast growing tropical species had improved board performance as compared to single species. All mechanical and physical properties evaluated met the requirements set by the EN 310:1994, EN 317:1994 and EN 319:1994 standards for general purpose used.